2023
DOI: 10.2196/45110
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Community Cohesion in Older Adults During the COVID-19 Epidemic: Cross-sectional Study

Abstract: Background The community environment plays a vital role in the health of older adults. During the COVID-19 epidemic, older adults, who were considered the most impacted and most vulnerable social group, were confined to their homes during the implementation of management and control measures for the epidemic. In such situations, older adults may have to contend with a lack of resources and experience anxiety. Therefore, identifying the environmental factors that are beneficial for their physical an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…En el diagnóstico participativo, se encontró que las personas ancianas valoran el vínculo con los clubes de personas su misma edad, las juntas de vecinos y vecinas, y los centros de salud, lo que evidencia lo importante que es la socialización en este grupo de población. La evidencia demuestra que el entorno comunitario interviene en la salud física y mental de las personas mayores y que un alto nivel de cohesión comunitaria se relaciona con una mejor percepción de salud y satisfacción con la vida 6 .…”
Section: Discussionunclassified
“…En el diagnóstico participativo, se encontró que las personas ancianas valoran el vínculo con los clubes de personas su misma edad, las juntas de vecinos y vecinas, y los centros de salud, lo que evidencia lo importante que es la socialización en este grupo de población. La evidencia demuestra que el entorno comunitario interviene en la salud física y mental de las personas mayores y que un alto nivel de cohesión comunitaria se relaciona con una mejor percepción de salud y satisfacción con la vida 6 .…”
Section: Discussionunclassified
“…Face-to-face structured interviews were conducted by Master of Public Health students who used a standardized interview protocol and a set of responses for recording the responses of participants. The interview time was approximately 45–60 min for most participants, and the interviewer suggested that elderly people who feel tired may take a rest [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Psychological resilience, also known as psychological elasticity, refers to a stable psychological characteristic that reduces, adapts to, or even overcomes the negative impact of sudden events on mental health ( 2 ). The existence of psychological resilience enables the public to self-regulate and cope with the emotional turmoil incurred by the diffusive crisis, which is crucial for maintaining mental health after such events ( 3 , 4 ). From the perspectives of safety informatics and information economics, the key to resolving diffusive crisis lies in information management, and the prevention of uncertain risks also depends on the extent of available information.…”
Section: Introductionmentioning
confidence: 99%